Inside Back Cover, Volume 41, Issue 1. Issue 1 (24th December 2019) - Hijazi, Hadia; Coelho, Fernanda S.; Gonzaga‐Jauregui, Claudia; Bernardini, Laura; Mar, Soe S.; Manning, Melanie A.; Hanson‐Kahn, Andrea; Naidu, SakkuBai; Srivastava, Siddharth; Lee, Jennifer A.; Jones, Julie R.; Friez, Michael J.; et al.
Abstract : Inside Back Cover : The cover image is based on the Research Article Xq22 deletions and correlation with distinct neurological disease traits in females: Further evidence for a contiguous gene syndrome by Hadia Hijazi et al., https://doi.org/10.1002/humu.23902 . Cover image © Hadia Hijazi & Ameerah Deyab Images.